Personal Finance and Investments / A Behavioural Finance Perspective - Redhead Keith (Routledge - Taylor & Francis Group, 2008)
This book will help the reader to grasp the relevant principles of money management. Preface, Introduction, The Psychology of Personal Investment Decisions, Basics of Money and Bond and Property Markets, Basic of Stocks Markets, Institutional Investments, Capital Market Theory, Portfolio Management, Investment Analysis, Market Efficiency, Stock Index Futures, Stock Options, International Investing: Using Currency Derivatives, Bond and Interest Rate Analysis, Glossary, References, Index.